2013
DOI: 10.1515/mlt-2013-0004
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Teachers for Urban Students Who Have Been Labeled as Having Special Needs

Abstract: Preparing teachers to work in urban public schools -and to remain there -is a daunting challenge. In an age plagued with the overrepresentation of culturally and linguistically diverse (CLD) students placed in special education programs, it is important that teacher preparation programs within the field of special education devote attention to the devastating effects of deficit thinking. The current focus on the achievement gap and poor graduation rates has highlighted the challenges facing urban schools and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The assumptions of interface between CTE and CRT are particularly relevant to understanding improvement in students' learning outcomes in general and special education. In addition, research has revealed that teachers in urban settings may garner a low sense of efficacy as a result of challenges faced in such environments (Bank et al, 2013;Tschannen-Moran & Hoy, 2007). As the majority of CLD students are educated in urban schools (Jacob, 2007), this study extends the existing literature on CTE by examining efficacy beliefs of urban special education teachers, a population that has not yet been investigated.…”
Section: Aims and Research Questionsmentioning
confidence: 92%
See 2 more Smart Citations
“…The assumptions of interface between CTE and CRT are particularly relevant to understanding improvement in students' learning outcomes in general and special education. In addition, research has revealed that teachers in urban settings may garner a low sense of efficacy as a result of challenges faced in such environments (Bank et al, 2013;Tschannen-Moran & Hoy, 2007). As the majority of CLD students are educated in urban schools (Jacob, 2007), this study extends the existing literature on CTE by examining efficacy beliefs of urban special education teachers, a population that has not yet been investigated.…”
Section: Aims and Research Questionsmentioning
confidence: 92%
“…However, the majority of teachers who work with students with disabilities from culturally and linguistically diverse (CLD) communities receive limited preparation on effective instruction for this population, leading teachers to question their ability to improve learning for these students (Cartledge & Kourea, 2008;Muller, Singer, & Carranza, 2006;Paneque & Barbetta, 2006). When special education teachers do not feel well prepared to provide culturally/ linguistically responsive instruction (e.g., Muller et al, 2006), they may be more likely to select instructional strategies based on students' disabilityrelated needs with little consideration of students' sociocultural and/or linguistic backgrounds (Artiles, Trent, & Palmer, 2004;Bank, Obiakor, & Algozzine, 2013;Garcia & Ortiz, 2008, 2013. This low teaching efficacy (personal teaching efficacy or self-efficacy, as well as outcome expectancy or teaching efficacy) is a concern because teachers with low efficacy are likely to be reluctant to try different ways to respond to unique needs for students with special needs (Accardo, Finnegan, Gulkus, & Papay, 2017;Chu, 2011;Chu & García, 2014;Hartmann, 2012;Woodcock & Vialle, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation